2012
DOI: 10.1017/s000711451200414x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Diet Quality Index for Adolescents by comparison with biomarkers, nutrient and food intakes: the HELENA study

Abstract: Food-based dietary guidelines (FBDG) aim to address the nutritional requirements at population level in order to prevent diseases and promote a healthy lifestyle. Diet quality indices can be used to assess the compliance with these FBDG. The present study aimed to investigate whether the newly developed Diet Quality Index for Adolescents (DQI-A) is a good surrogate measure for adherence to FBDG, and whether adherence to these FBDG effectively leads to better nutrient intakes and nutritional biomarkers in adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(121 citation statements)
references
References 56 publications
5
99
0
9
Order By: Relevance
“…The prevalence of risk factors for obesity is fairly high among the adolescents. This study shows that a great proportion of overweight/ obese children and adolescents had correct dietary habits (Vyncke et al 2013) and confirm that genetic factors, and in particular the I148M variant of PNPLA3, play a major role in the development and severity of steatosis in obesity during the developmental age, representing by far the strongest determinant. These and previous data (Valenti et al 2010b) suggest that severe steatosis and NASH behave similarly to a monogenic disease in obese individuals during the developmental age.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The prevalence of risk factors for obesity is fairly high among the adolescents. This study shows that a great proportion of overweight/ obese children and adolescents had correct dietary habits (Vyncke et al 2013) and confirm that genetic factors, and in particular the I148M variant of PNPLA3, play a major role in the development and severity of steatosis in obesity during the developmental age, representing by far the strongest determinant. These and previous data (Valenti et al 2010b) suggest that severe steatosis and NASH behave similarly to a monogenic disease in obese individuals during the developmental age.…”
Section: Discussionsupporting
confidence: 71%
“…In conclusion, despite likely increased caloric intake, obese adolescents report an apparently almost correct dietary pattern (Vyncke et al 2013). The severity of the hepatic complication resulting from insulin resistance, i.e.…”
Section: Discussionmentioning
confidence: 77%
“…The Diet Quality Index Revised developed by Hains et al (51) was reported to correlate with plasma biomarkers (52) for micronutrient intake. Dietary variety and diversity were shown to be associated with nutrient adequacy (53) , biomarkers (54) and lower disease risk (55) . These indices, with some modifications, have been used previously in Mexicans (41) , Haitian immigrants in Canada (56) and a sample of the African population (40) , but not in a nationally representative sample.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 The DQI-A consists of 3 principles forming the basis of a healthy diet: dietary equilibrium, dietary diversity, and dietary quality. 48,49 A final DQI-A score was calculated, with a higher score indicating a better-quality diet. The validity of the HELENA-DIAT and the DQI-A has been confirmed elsewhere.…”
Section: Nutritional Assessmentmentioning
confidence: 99%